Monitoring Renewable Energy Dengan Konsep Mini SCADA Menggunakan IoT - Wahyu Pratama , Muhammad Syafii ; Tridianto, Erik; Permatasari, Prima Dewi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
The supply of electricity for the people of Indonesia is still dependent on PLN. PLN as a company that provides electrical energy often experiences problems that result in rotating blackouts due to peak load and theft which impact on consumers. In this research renewable energy monitoring has been designed using the mini scada concept which is integrated with IoT. The Miniscada concept has the advantage of being able to monitor the amount of electricity generated by renewable energy online, realtime and together wirelessly. By using the SCADA concept which has the function ckient and server. Client as a transmitter is used as a place to read data from the sensor before it is sent to the server. The server as a receiver is used as a place to store data sent by the transmitter and can be monitored online and in real time. The server receives all information on the amount of electricity emitted through the transmitter using a 2.4Ghz frequency radio and uploads the amount of electricity from the server to the cloud platform Blynk application. By utilizing IoT technology that makes it easy to monitor data in the form of voltage and current from solar panels, wind turbines and PLN with IoT via a smartphone. So that the data obtained in the form of AC voltage with 0.9% error DC voltage from Solar Panels with error 1.89% AC current from incandescent lamps 25 watts with error 0.7% DC current from batteries with an error of 3%.